Caracterización zootécnica y genética de la población de cuyes en el caserío de Coina - Usquil - Otuzco - La Libertad - Romero Marceliano, Miriam Raquel (2017)
This research was carried out with the objective of determining the zootechnical and genetic characterization of the guinea pig population. It was recorded by observation of its phenotypic characteristics, measures of their zoometric, morphological and productive characteristics. A total of 356 guinea pigs were evaluated using a structured interview and fieldwork. The data were processed using Excel to calculate descriptive statistics and to format tables andgraphs. It was found that the guinea pigs that breed in Coina according to their body shape are of the type A, with black eye color, coloration of the predominant coat is sorrel overo and its coat form is Type 1. The percentage of fertility indicates 82.02% the litter size is between 1 to 4 offspring. The productive characteristics of guinea pigs in the research area have a zoommetric association with Andina, Inti and Peru improved cuyes. The zootechnical characterization of guinea pigs in Coina coincides, mainly with the improved criollo breed, from medium to high production and productivity